Kepemimpinan Pengasuh Dalam Mewujudkan Santri Yang Berdaya Saing Di Pondok Pesantren Fathul Ulum Diwek Jombang - Sukron Makmun; Hermanto; Shohib (4, 2025)
The implementation of the Independent Curriculum at MI Miftahul Khoir 1 Karangrejo aims to restore the education system after the Covid-19 pandemic, as well as improve student competence. Since 2023, the implementation of the Independent Curriculum in the school has had a challenging impact. This research aims to: (1) Assess the implementation of the Independent Curriculum. (2) Analyze the expansion of PAI learning achievement to improve learning outcomes. (3) Identify supporting and inhibiting factors for the implementation of the Independent Curriculum. This study uses a subjective strategy with a contextual investigation approach. Primary data was obtained from grade I and IV teachers through interviews, observations, and documentation. The purpose of the research is to describe the facts in the field. The results of the study showed: (1) The implementation process of the Independent Curriculum starts from preparation, workshops, pragmatic learning, to assessment. (2) Daily student behavior and increase in student grades showed an increase in PAI learning outcomes. (3) Supporting and inhibiting factors for the implementation of the Independent Curriculum consist of internal factors such as student motivation and external factors such as school strategy. Abstrak Penerapan Kurikulum Merdeka di MI Miftahul Khoir 1 Karangrejo bertujuan memulihkan sistem pendidikan pasca pandemi Covid-19, serta meningkatkan kompetensi siswa. Sejak tahun 2023, implementasi Kurikulum Merdeka di sekolah tersebut menimbulkan dampak yang menantang. Penelitian ini bertujuan: (1) Menilai implementasi Kurikulum Merdeka. (2) Menganalisis perluasan prestasi pembelajaran PAI untuk meningkatkan hasil belajar. (3) Mengidentifikasi faktor pendukung dan penghambat implementasi Kurikulum Merdeka. Penelitian ini menggunakan strategi subjektif dengan pendekatan investigasi kontekstual. Data primer diperoleh dari guru kelas I dan IV melalui wawancara, observasi, dan dokumentasi. Tujuan penelitian adalah mendeskripsikan fakta di lapangan. Hasil penelitian menunjukkan: (1) Proses implementasi Kurikulum Merdeka dimulai dari persiapan, workshop, pembelajaran pragmatis, hingga penilaian. (2) Perilaku siswa sehari-hari dan peningkatan nilai siswa menunjukkan peningkatan hasil belajar PAI. (3) Faktor pendukung dan penghambat implementasi Kurikulum Merdeka terdiri dari faktor internal seperti motivasi siswa dan faktor eksternal seperti strategi sekolah.